Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1189/jlb.1203652
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptors that mediate B cell homing to secondary lymphoid tissues are highly expressed in B cell chronic lymphocytic leukemia and non-Hodgkin lymphomas with widespread nodular dissemination

Abstract: B cell neoplasms present heterogeneous patterns of lymphoid organ involvement, which may be a result of the differential expression of chemokine receptors. We found that chemokine receptor (CCR)7, CXC chemokine receptor (CXCR)4, or CXCR5, the main chemokine receptors that mediate B cell entry into secondary lymphoid tissues and their homing to T cell and B cell zones therein, were highly expressed in B malignancies with widespread involvement of lymph nodes. Conversely, those pathologies with little or no nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 52 publications
8
144
0
Order By: Relevance
“…CLL B cells show a marked tendency to invade the LNs (17), and we have demonstrated that the ability of these cells to migrate in response to CCR7 ligands correlates with lymphadenopathy, suggesting a functional role of CCR7 in guiding CLL cells to LNs (16). In addition, it has been reported a strong correlation between the expression of CCR7 by solid tumor cells and the presence of LN metastases (2).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…CLL B cells show a marked tendency to invade the LNs (17), and we have demonstrated that the ability of these cells to migrate in response to CCR7 ligands correlates with lymphadenopathy, suggesting a functional role of CCR7 in guiding CLL cells to LNs (16). In addition, it has been reported a strong correlation between the expression of CCR7 by solid tumor cells and the presence of LN metastases (2).…”
Section: Introductionmentioning
confidence: 83%
“…We have previously described a high expression of CCR7 in those B-cell neoplasms that are characterized by the infiltration of secondary lymphoid tissue, like chronic lymphocytic leukemia (CLL) (16). CLL B cells show a marked tendency to invade the LNs (17), and we have demonstrated that the ability of these cells to migrate in response to CCR7 ligands correlates with lymphadenopathy, suggesting a functional role of CCR7 in guiding CLL cells to LNs (16).…”
Section: Introductionmentioning
confidence: 93%
“…34,35 Recently, it has been suggested that, in leukemic B cell lymphomas, CXCR5 may be associated with the spread of malignant B cells to lymphoid tissues. 40,41 Here, we show the abundant expression of CXCR5 transcripts and the presence of surface CXCR5 on SCC cells. Our observation is consistent with the concept that metastasis and leukocyte trafficking share underlying mechanisms and suggests that CXCL13/CXCR5 interactions may provide a novel complementary pathway, mediating lymphogenic spread.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL13 was found to be significantly elevated in serum of B-CLL patients and seems to correlate with ß2-microglobulin serum levels [52][53][54]. Furthermore, the CXCL13/CXCR5 axis has been demonstrated to be part of an interesting mechanism of apoptosis inhibition in B-CLL cells: CXCL13/CXCR5, together with CCL19/CCR7, enhance the expression of the paternally expressed gene 10 (PEG10) in CD23 + CD5…”
Section: Cxcl13 and Its Receptor Cxcr5mentioning
confidence: 99%
“…CCL19 and CCL21 are expressed in the T cell zone of secondary lymphoid, mucosa-associated lymphoid tissue and high endothelial venules, but not in the B cell areas or sinuses or blood-derived leukocytes [54]. They are the known ligands of the chemokine receptor CCR7 which is a crucial receptor for trafficking of B lymphocytes as well as T lymphocytes and DCs across high endothelial venules and for positioning in T cell zones of secondary lymphoid organs (Fig.…”
Section: Ccl19 Ccl21 and Their Common Receptor Ccr7mentioning
confidence: 99%